2018
DOI: 10.3847/2041-8213/aac722
|View full text |Cite
|
Sign up to set email alerts
|

The R-Process Alliance: 2MASS J09544277+5246414, the Most Actinide-enhanced R-II Star Known

Abstract: We report the discovery of a new actinide-boost star, 2MASSJ09544277+5246414, originally identified as a very bright (V = 10.1), extremely metal-poor ([Fe/H] = −2.99) K giant in the LAMOST survey, and found to be highly r-process-enhanced (r-II; [Eu/Fe] = +1.28]), during the snapshot phase of the R-Process Alliance (RPA). Based on a high signal-to-noise ratio (S/N), high-resolution spectrum obtained with the Harlan J. Smith 2.7 m telescope, this star is the first confirmed actinide-boost star found by RPA eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 43 publications
1
101
3
Order By: Relevance
“…Actinide abundances in metal-poor stars could hold the key to disentangle the hydrodynamical environment(s) of the r-process. The existence of stars with super-and sub-solar actinide yields (Schatz et al 2002;Roederer et al 2009a;Holmbeck et al 2018;Ji & Frebel 2018) possibly indicate varying r-process conditions. The fact that all currently known actinide-boost stars are very metal-poor ([Fe/H] −2.0) is another interesting finding.…”
Section: Actinidesmentioning
confidence: 99%
“…Actinide abundances in metal-poor stars could hold the key to disentangle the hydrodynamical environment(s) of the r-process. The existence of stars with super-and sub-solar actinide yields (Schatz et al 2002;Roederer et al 2009a;Holmbeck et al 2018;Ji & Frebel 2018) possibly indicate varying r-process conditions. The fact that all currently known actinide-boost stars are very metal-poor ([Fe/H] −2.0) is another interesting finding.…”
Section: Actinidesmentioning
confidence: 99%
“…However, the conditions in the ejecta differ considerably (i.e., electron fraction, entropy, and ejecta velocity), which leaves an imprint on the compositions. Hansen et al (2018) and the recently discovered actinide-boost star J09544277+5246414 (Holmbeck et al 2018). In addition, we also include the Reticulum II star with known Th yield, DESJ033523-540407 (Ji & Frebel 2018).…”
Section: Actinide and Lanthanide Yields In Our Modelsmentioning
confidence: 99%
“…Even before these observations, theoretical calculations have shown that actinide production in the r-process can vary depending on the conditions and the nuclear mass model (e.g., Goriely & Clerbaux 1999). An overview on actinide-boost stars has been given in Roederer et al (2009), with more recent discoveries by Mashonkina et al (2014) and Holmbeck et al (2018). Ji & Frebel (2018), on the other hand, have measured the Th abundance of DES J033523−540407, a star in the r-process-enriched ultra-faint dwarf galaxy Reticulum II, and their result suggests that this star might belong to a different, actinide-deficient category of stars.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main reasons for this: 1) The enhancement in r-process elements ensures that spectral lines from a wide variety of r-process elements are sufficiently strong to be measured, while the (relative) lack of metal lines (compared to more metal-rich stars) reduces the severe blending typically seen in the blue spectral region; and 2) These stars are selected to have little-to-no contamination from the slow (s-) process, simplifying comparisons with models of r-process yields. If the enhancement in radioactive elements like Th and U is sufficiently high, cosmo-chronometric ages can also be determined (see, e.g., Holmbeck et al 2018a and references therein).…”
Section: Introductionmentioning
confidence: 99%